Antioxidant Effect of Liquid Smoke on Oxidation Stability of Catfish (Clarias gariepinus) Smoke Sausage During Storage - Ernawati, Ernawati; Purnomo, Hari; Estiasih, Teti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
Fish meat are very susceptible to oxidation because a lot of unsaturated fatty acids. Processing of fish sausage with smoking will provide natural antioxidants, namely phenols contained in the components of smoke. The aim of this research was to study the antioxidant effects of liquid smoke to the oxidation stability of fish sausage catfish (Clarias gariepinus) during storage. Randomized studies using Design Group (RAK) with a liquid smoking treatment and storage time on the sausage at 60 Â°C. Parameter used for oxidative deterioration indicators is the peroxides value and TBARS value. The result showed that the treatment liquid can suppress oxidation during storage. Oxidation during storage of smoked sausage is lower than the oxidation of sausage without curing. Smoked sausage tended to be more stable during storage for 60 hours at 60 Â°C instead of sausage without curing. Key words: antioxidant, phenol, sausage, peroxides value, thibarbituric acid reactive substances